The Effect Of Critical Thinking Skills, Computer Knowledge, and Learning Facilities On The Academic Achievement Of Students In The Accounting Vocational Program At Public Vocational High Schools In East Jakarta - Freesta Azzahra Kurniaputri; Ati Sumiati; Wahyu Lestari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The purpose of this study is to determine the influence of critical thinking skills, computer knowledge, and learning facilities on the learning outcomes of students in the accounting vocational program at public vocational high schools in the East Jakarta region. The research method used was a quantitative approach with proportional random sampling. The sample consisted of 108 students from three public vocational high schools in East Jakarta: SMK Negeri 22 Jakarta, SMK Negeri 40 Jakarta, and SMK Negeri 51 Jakarta. Research data were collected via questionnaires and analyzed using a t-test in accordance with the research objectives. The results of the study indicate that critical thinking skills, computer knowledge, and learning facilities have a positive and significant influence on student learning outcomes in the Spreadsheet course.